Principal's Strategy in Improving the Quality of Graduates at SMA Negeri 1 Batusangkar - Wira Astuty; Suswati Hendriani; Sufyarma Marsidin (IAIN Batusangkar, 2021)
The graduates quality is an indicator of the school success in carrying out its function to improve the quality of graduates at schools. To improve graduates quality, the principal plays an important role in applying his/her roles, functions and strategies. This study aims to examine the strategies used by the principal in improving graduates quality in SMA Negeri 1 Batusangkar. The methodology used in this research is qualitative descriptive method in form of case study. Case study research aims to reveal a case that occured in a certain place at a certain time. The result of this study indicated that there are three main strategies applied by the principal in improving graduates quality both in quality and quantity. These strategies are through the superior program owned by the school, the strategy of developing work program for principal deputies of each field (curriculum, students-realtions, public relations, and facilities), and the strategy for developing the quality of human resources, including students. The recommendations and suggestions from this research for the future is the principal can cooperate optimally with those involved in the school to be able to develop strategies, models, teachniques, methods and approaches to improve graduates quality.